Pengaruh Pemberian Lumpur Padat Limbah Pabrik Kelapa Sawit Terhadap Ketersediaan Hara Pada Tanah Podsolik Dan Produksi Tanaman Jagung: The Effect of Providing Solid Sludge from Palm Oil Mill Waste on Nutrient Availability in Podsolic Soil and Corn Plant Production - Fidela Shabrina; Muhammad Syarbini; Abdul Hadi (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2025)
Podzolic soil fertility and health are generally low due to its poor physical and chemical properties. Consequently, the use of organic soil amendments is essential to improve these properties and provide essential nutrients. Palm oil mill sludge solid waste is rich in nitrogen, phosphorus, potassium, magnesium and calcium which makes it a suitable fertilizer. This study aimed to evaluate the effect of palm oil mill sludge solid waste application on the availability of nitrogen, phosphorus and potassium in podzolic soil and corn (Zea mays) production. The experiment was conducted in a pot using a single factor Completely Randomized Design (CRD). The findings showed that application of palm oil mill sludge solid waste to podzolic soil increased the availability of nutrients N-NH4+, N-NO3-, available P and available K and the fresh and dry weight of corn plants. However, it did not increase soil pH. Treatment P4 (20 t ha-1) produced the highest values ​​of N-NH4+, N-NO3-, available P, available K and the fresh and dry weight of corn plants, making it the most effective treatment for the utilization of palm oil mill sludge on Podzolic soil.